Peran Orang Tua dalam Pembentukan Etika Berkomunikasi Anak di Kota Surabaya - Binta KH; Ratri Adinda Oktavdianti (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Parents have an important and primary role in the formation of children's communication ethics. Instilling ethics in children themselves is done so that children can grow with the truth and goodness of how to act in their social environment. Because basically communication ethics is a basic part of daily activities, communication becomes a link between one individual and another. In addition, ethics in communication can also describe or reflect our self-image to others and vice versa.The problem in this study is that most parents, especially in the city of Surabaya, do not understand the importance of forming children's communication ethics. This study aims to find out how the role of parents in the formation of children's communication ethics in the city of Surabaya. This type of qualitative research, is qualitative descriptive in nature and the data obtained through interview observation techniques, and documentation in the field.The results show that through observation techniques and interviews in the field that the role of parents in the formation of children's communication ethics in the city of Surabaya is very important for the growth and development of children.